2018
DOI: 10.1007/s12035-018-0973-4
|View full text |Cite
|
Sign up to set email alerts
|

SLAB51 Probiotic Formulation Activates SIRT1 Pathway Promoting Antioxidant and Neuroprotective Effects in an AD Mouse Model

Abstract: The gut-brain axis is a bidirectional communication network functionally linking the gut and the central nervous system (CNS). Based on this, the rational manipulation of intestinal microbiota represents a novel attractive therapeutic strategy for the treatment of CNS-associated disorders. In this study, we explored the properties of a probiotic formulation (namely SLAB51) in counteracting brain oxidative damages associated with Alzheimer’s disease (AD). Specifically, transgenic AD mice (3xTg-AD) were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(156 citation statements)
references
References 74 publications
10
145
0
1
Order By: Relevance
“…Lastly, Bonfili et al (2017) determined that the expression levels of Beclin 1 and LC-II, autophagy regulator genes, significantly increased. More recently, Bonfili et al (2018) have investigated how SLAB51 activates antioxidative and neuroprotective mechanisms in 3xTg-AD mice, and determined SLAB51 activated Sirtuin 1 pathway (SIRT1: an NAD + -dependent protein deacetylase). They confirmed this finding by indicating an increase in acetylation level of SIRT1's substrate RARb.…”
Section: Regulation Of Neuronal Proteolysismentioning
confidence: 99%
“…Lastly, Bonfili et al (2017) determined that the expression levels of Beclin 1 and LC-II, autophagy regulator genes, significantly increased. More recently, Bonfili et al (2018) have investigated how SLAB51 activates antioxidative and neuroprotective mechanisms in 3xTg-AD mice, and determined SLAB51 activated Sirtuin 1 pathway (SIRT1: an NAD + -dependent protein deacetylase). They confirmed this finding by indicating an increase in acetylation level of SIRT1's substrate RARb.…”
Section: Regulation Of Neuronal Proteolysismentioning
confidence: 99%
“…Probiotics are defined as 'live microorganisms which when administered in adequate amounts confer a health benefit on the host' (FAO/WHO, 2006) and have been demonstrated to play a role in maintaining microbial homeostasis within the gut (Kumar et al, 2016;Umbrello and Esposito, 2016). Indeed, probiotic organisms have shown beneficial effects on neurodegenerative disorders (Akbari et al, 2016;Bonfili et al, 2017Bonfili et al, , 2018Kobayashi et al, 2017;Nimgampalle and Kuna, 2017) and animal studies with probiotics have shown clear neuroprotective effects (Ait-Belgnaoui et al, 2014;Distrutti et al, 2014;Möhle et al, 2016;Park et al, 2017). The aetiology of neurodegeneration is complex and the functional diversity of probiotics may facilitate the simultaneous targeting of multiple disease-related mechanisms (Elufioye et al, 2017;Faden and Stoica, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…First reports indicate successful application in animal models: Lactobacillus plantarum, for example, was able to restore cognition and levels of acetylcholine esterase in the brain of a D-galactose-evoked AD-like rat model [94]. Similar results were obtained from investigations using genetic AD mouse models with Bifidobacterium breve strain A1 [95], SLAB51 (probiotic formulation, [96]) but also with Lactobacillus acidophilus, Lactobacillus fermentum, Bifidobacterium lactis, and Bifidobacterium longum in rodent sporadic AD models due to amyloid-β injection [97][98][99]. As only one explorative intervention study reports on a small cohort of AD human patients [100], the usefulness in humans is still not proven.…”
Section: Therapeutic Strategies Derived From Microbes Against Human Amentioning
confidence: 64%